2001
DOI: 10.1103/physrevb.63.184304
|View full text |Cite
|
Sign up to set email alerts
|

Theory of bound polarons in oxide compounds

Abstract: We present a multilateral theoretical study of bound polarons in oxide compounds MgO and α-Al 2 O 3 (corundum). A continuum theory at arbitrary electron-phonon coupling is used for calculation of the energies of thermal dissociation, photoionization (optically induced release of an electron (hole) from the ground self-consistent state), as well as optical absorption to the nonrelaxed excited states. Unlike the case of free strong-coupling polarons, where the ratio κ of the photoionization energy to the thermal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…Furthermore, many theoretical studies of defects in Al 2 O 3 have been reported based on classical interatomic potential [6][7][8][9][10], semi-empirical [11][12][13], Hartree-Fock [14], density functional [15,16], and most recently hybrid density functional methods [17,18]. Many of these studies have focused on the F-centre associated with oxygen vacancy formation, while the nature of oxygen interstitial structure and spin configuration has received much less attention.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, many theoretical studies of defects in Al 2 O 3 have been reported based on classical interatomic potential [6][7][8][9][10], semi-empirical [11][12][13], Hartree-Fock [14], density functional [15,16], and most recently hybrid density functional methods [17,18]. Many of these studies have focused on the F-centre associated with oxygen vacancy formation, while the nature of oxygen interstitial structure and spin configuration has received much less attention.…”
Section: Introductionmentioning
confidence: 98%
“…Recently the interest in the polaron and bipolaron subject field has surfaced again due to an expansion of this field of investigations to anisotropic crystals, low dimensional structures and systems with quantum wells [7,[10][11][12][13]. The problem of the choice of a bipolaron spatial configuration and consideration of electron correlations is actual for such systems, too.…”
Section: Introductionmentioning
confidence: 99%
“…Quasi-two-dimensional (2D) systems, including surfaces, heterointerfaces and layered materials, have become a rich playground for discovering exotic electronic effects such as high T c -superconductivity and novel magnetic phases [1][2][3][4][5]. The formation of polarons and the modification of their properties by reduced dimensionality have been implicated in many of these phenomena [1,[6][7][8]. Although a number of systems, including layered transition-metal oxides [5], surfaces and thin insulating films [9,10] are suspected to exhibit 2D polaronic behavior, directly probing their properties remains extremely challenging.…”
mentioning
confidence: 99%